Wheat straw decomposition, N-mineralization and microbial biomass after 5 years of conservation tillage in Gleysol field - Andrej TURK; Rok MIHELIČ (Acta Agriculturae Slovenica, 2013)
Long-term field experiment to follow various effects of conservation soil tillage is conducted at Biotechnical faculty in Ljubljana. The soil is Eutric Gleysol. Conventional treatment with plowing, 22 cm deep P, and conservation treatment by rotary harrow to a depth of 10 cm N, and subplots with compost amendment (-c) and without fertilization (-n) were observed. After 5 years nutrient contents and organic matter were higher in N than P. Compost addition had a positive effect on microbial biomass, but the tillage system did not affect it. However, nitrogen mineralization and decomposition of straw were higher in P as in N, and in the soil depth of 15 – 20 cm than in the 5 – 10 cm.